Analysis of the level of implementation of basic environmental management instruments in northeast municipalities in 2017 (Research, Society and Development, 2021)
This article aimed to analyze the level of implementation of basic environmental management instruments in northeastern municipalities in 2017. For this purpose, data from the survey Profile of Brazilian Municipalities - 2017 published by the Brazilian Institute of Geography and Statistics (IBGE) are used. The work adopts as an empirical strategy, the creation of the Environmental Management Index (IGA) for municipalities in the Northeast. The results obtained show that the level of implementation of the considered management instruments have, on average, low rates in the region's municipalities. Municipalities that implemented the four management instruments considered percentages compared to the whole. It was also observed that the less frequent instrument is the existence of an exclusive municipal secretariat for the environment. Based on the research, it is possible to observe that municipalities in the Northeast are still silent on the implementation of the instruments considered and the lack of interest from public administrations regarding environmental management is still an obstacle in most municipalities.